GIS wind energy a case of UAE. - Yagoub, M. M. (International Journal of Geoinformatics)
In this study, the mean monthly wind speed complemented by remote sensing and GIS spatial and statistical analysis are utilized to identify suitable areas for wind energy generation in UAE. The suitable areas are found along the north-western coastal areas of ABU Dhabi. The areas are weighted based on the wind energy generation capacity and proximity to the demand centers (urban, agriculture, ports, refineries, airports, etc.) roads and transmission lines. The wind energy locations identified can be utilized to meet the increasing demands arise from population increase and the rapid development. The study demonstrate unique combination of physical, climatic, and socio-economic variables.